INFORMAL FINANCING OF CANDIDATES: IMPACT OF INFORMAL SOCIAL NETWORK ON CAMPAIGN COST - Syahrin Badrin Kamahi; Yonathan H.L Lopo; Frans B.R Humau; Esrah D.N.A Benu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article discusses the impact of cultural context and informal social networks on candidate campaign financing in the Malaka Regency regional elections, East Nusa Tenggara Province. This study employs a qualitative approach, incorporating clientelism and candidate financing theories, to examine candidate financing practices in the Malaka Regency elections. The study's main finding is that all candidate pairs in the elections utilized informal networks based on kinship, ethnicity, and organizations as political vehicles. However, these informal networks did not significantly influence campaign funding. The study concludes that the primary component of candidate financing remains dominated by political party machinery, while informal networks do not receive sufficient financing as political machines.